2016
DOI: 10.18632/oncotarget.13076
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of long noncoding RNA H19 overexpression in human solid tumors: evidence from a meta-analysis

Abstract: BackgroundMany studies have reported that the expression level of lncRNA H19 was increased in various tumors. LncRNA H19 may play a significant role in cancer occurrence and development. An increased level of H19 was also associated with poor clinical outcomes of cancer patients.Results12 eligible studies were screened, with a total of 1437 cancer patients. From the results of meta-analysis, as for prognosis, the patients with high expression of lncRNA H19 were shorter in OS (HR=1.08, 95% CI: 1.05-1.12). Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Aberrant expression of lncRNAs exerts impacts on the tumor biological processes and often correlated with aggressive progression and prognosis. Consequently, lncRNAs, as promising biomarkers for tumor prognosis and monitoring, have attracted great attentions [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of lncRNAs exerts impacts on the tumor biological processes and often correlated with aggressive progression and prognosis. Consequently, lncRNAs, as promising biomarkers for tumor prognosis and monitoring, have attracted great attentions [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that lncRNAs counted much in modifying the chemo‐sensitivity, for instance, up‐regulated lncRNA lncARSR was observed to promote doxorubicin resistance in HCC via modulating PTEN‐PI3K/Akt pathway . Of note, lncRNA H19, a paternally imprinted gene located in 11p15.5, was increasingly found to be over‐expressed within various cancers, including HCC, glioblastoma, gallbladder cancer, gastric cancer, and so on . To be specific, inhibition of lncRNA H19 and miR‐675 expression may promote migration and invasion of HCC cells though AKT/GSK‐3β/Cdc25A signaling pathways .…”
Section: Introductionmentioning
confidence: 99%
“…10 Of note, lncRNA H19, a paternally imprinted gene located in 11p15.5, was increasingly found to be over-expressed within various cancers, including HCC, glioblastoma, gallbladder cancer, gastric cancer, and so on. [11][12][13][14] To be specific, inhibition of lncRNA H19 and miR-675 expression may promote migration and invasion of HCC cells though AKT/GSK-3β/Cdc25A signaling pathways. 15 Hence, it was hypothesized that lncRNA H19 might play an oncogenic role in HCC, and also it might affect the chemo-and radio-tolerance of HCC.…”
mentioning
confidence: 99%
“…MiR-675, which is known as one of the most important transcripts in the H19 locus, is located at exon 1 and implicated in the carcinogenesis and tumor invasiveness [11]. LncRNA H19 has been reported to be predictive of clinicopathological characteristics and H19 expression was associated with histological grades, clinical stages and lymph node metastasis status using a meta-analysis [12,13].…”
Section: Ivyspringmentioning
confidence: 99%